To solve the equation 1 + (2 + x) = 9, you can follow these steps:
1. Start by simplifying the equation inside the parentheses.
(2 + x) becomes 2 + x.
2. Now, substitute the simplified expression back into the original equation.
1 + (2 + x) = 9 becomes 1 + (2 + x) = 9.
3. Simplify the equation further.
1 + 2 + x = 9.
4. Combine like terms.
3 + x = 9.
5. Subtract 3 from both sides of the equation to isolate the x variable.
x = 9 - 3.
6. Perform the subtraction on the right side.
x = 6.
So, the solution to the equation 1 + (2 + x) = 9 is x = 6.
1+[2+x]=9
1 answer